Pertumbuhan Penjualan, Leverage dan Kebijakan Dividen - Wijaya, Odith Laxmana; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi; Vol 32 No 11 (2022)DO - 10.24843/EJA.2022.v32.i11.p15, 2022)
The aim of this research is to empirically examine the effect of sales growth and leverage on dividend policy. The quantitative approach was chosen in this research by using data from the coal industry listed on the Indonesia Stock Exchange. Financial data from 23 coal companies were analyzed using multiple linear regression analysis. As expected, this research results reveal that sales growth has a significant negative effect on dividend policy. The results of this study indicate that dividends are paid after the issuer has completed its investment expenditures related to efforts to increase sales. This is in accordance with the theory of residual dividend policy. On the other hand, the results of this study find that leverage has a significant positive effect on dividend policy. Keywords: Sales Growth; Leverage; Dividen Policy